2020
DOI: 10.1136/tobaccocontrol-2019-055239
|View full text |Cite
|
Sign up to set email alerts
|

LGBT young adults’ awareness of and receptivity to the This Free Life tobacco public education campaign

Abstract: PurposeThis study measures awareness of and receptivity to the Food and Drug Administration’s This Free Life campaign seeking to change tobacco-related attitudes and beliefs among lesbian, gay, bisexual and/or transgender (LGBT) young adults.MethodsParticipants were young adults who self-identify as LGBT. The evaluation uses a treatment-control design. This study includes data from four survey rounds with participants from each round invited to participate in subsequent rounds and new participants invited to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…Preliminary evaluation findings showed that two years into the 3-year campaign, This Free Life had reached more than half of LGBT young adults surveyed in campaign-targeted treatment markets, with significantly higher campaign awareness in treatment markets than in control markets that had minimal campaign exposure. 16 Perceived effectiveness (ie, ad receptivity) 17 , 18 of campaign ads ranged from neutral to positive, suggesting that ads were generally well-received by the audience. 16 Additionally, the more a respondent identified with the LGBT community, the more receptive they were to campaign advertisements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary evaluation findings showed that two years into the 3-year campaign, This Free Life had reached more than half of LGBT young adults surveyed in campaign-targeted treatment markets, with significantly higher campaign awareness in treatment markets than in control markets that had minimal campaign exposure. 16 Perceived effectiveness (ie, ad receptivity) 17 , 18 of campaign ads ranged from neutral to positive, suggesting that ads were generally well-received by the audience. 16 Additionally, the more a respondent identified with the LGBT community, the more receptive they were to campaign advertisements.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Perceived effectiveness (ie, ad receptivity) 17 , 18 of campaign ads ranged from neutral to positive, suggesting that ads were generally well-received by the audience. 16 Additionally, the more a respondent identified with the LGBT community, the more receptive they were to campaign advertisements. 19 To the extent that self-reported awareness is correlated with objective measures of exposure to digital advertising, 20 the campaign awareness and receptivity levels achieved by This Free Life are suggestive of early campaign implementation success.…”
Section: Introductionmentioning
confidence: 99%
“…Running effective public health education campaigns requires organizations to tailor messages and provide outreach that resonates with their target audience. For example, the US Food and Drug Administration (FDA) Center for Tobacco Products has developed separate public education campaigns on the health consequences of tobacco products for at-risk teens [1]; lesbian, gay, bisexual, and transgender young adults [2]; multicultural youth [3]; rural male teens [4]; and adult smokers [5]. With increased media consumption and interpersonal interactions occurring online, social media platforms have become important in both engaging target audiences in public education campaigns and in understanding behaviors and perceptions around emerging public health issues across these target audiences.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significance and urgency of reducing tobacco use among LGB people, there have been few LGB-targeted anti-tobacco campaigns in the U.S. [ 10 ]. In addition, few studies have attempted to understand tobacco use interventions among LGB people [ 11 ].…”
Section: Introductionmentioning
confidence: 99%